2014
DOI: 10.1111/maec.12227
|View full text |Cite
|
Sign up to set email alerts
|

Low calcification rates and calcium carbonate production in Porites panamensis at its northernmost geographic distribution

Abstract: Porites panamensis is a hermatypic coral present in the eastern Pacific Ocean. Skeletal growth parameters have been reported, but studies of the relationship between annual calcification rates and environmental controls are scarce. In this study, we investigated three aspects of the annual calcification rates of P. panamensis: growth parameters among three P. panamensis populations; the sea surface temperature as a calcification rate control spanning a latitudinal gradient; and calcium carbonate production amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
0
13
0
9
Order By: Relevance
“…Our results further show that curve‐shaped seasonal temperature growth responses due to localized acclimation (e.g., for Galaxea spp. and Acropora dowingi ; Marshall & Clode, ; Vajed Samiei et al, ) and the positive relationship between temperature and calcification rates along tropical temperature gradients (e.g., for Montastraea and Porites ; Carricart‐Ganivet, ; Lough & Barnes, ; Lough et al, ; Norzagaray‐López et al, ) may be species‐ and location‐specific and not generally applicable to all coral genera, particularly those whose range extends to subtropical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further show that curve‐shaped seasonal temperature growth responses due to localized acclimation (e.g., for Galaxea spp. and Acropora dowingi ; Marshall & Clode, ; Vajed Samiei et al, ) and the positive relationship between temperature and calcification rates along tropical temperature gradients (e.g., for Montastraea and Porites ; Carricart‐Ganivet, ; Lough & Barnes, ; Lough et al, ; Norzagaray‐López et al, ) may be species‐ and location‐specific and not generally applicable to all coral genera, particularly those whose range extends to subtropical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of morphologic and growth variability in the reef structure, limited studies have been performed on massive corals (Graus and MacIntyre, 1982;Tomascik, 1990;Van Veghel and Bosscher, 1995;Smith et al, 2007). These include the reported by Norzagaray-López et al (2014) who found growth differences between columnar and encrusting colonies, nevertheless it is important to highlight that these differences were possibly biased by the effect of the gender and latitudinal gradients variations. To date, a comparison of the growth of different morphotypes including the gender effect in Poritid corals has not been undertaken, though it seems reasonable to speculate that columnar, massive and free-living forms may calcify at different rates in each specific gender.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown the systematics of calcification to differ among taxa and ocean regions. While temperature tends to boost calcification rates in recent z corals, temperature effects on extension rate and density markedly differ (Carricart-Ganivet, 2004;Elizalde-Rendon et al, 2010;Lough, 2008;Norzagary-Lopez et al, 2014). In the IndoPacific genus Porites, linear extension rate shows a significant increase with sea-water temperature but a concomitant decrease in bulk skeletal density (Lough, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Upon microscopic investigation using SEM ( Fig. 2a-g), the skeletons display stacked spherulites or fans and layers of fibrous aragonite which represent the microstructures typical of scleractinian corals (Constantz, 1986;Nothdurft and Webb, 2007). Within the centres of the single calcifying units (sclerodermites), porosity is more or less enhanced and the aragonite crystallites are particularly small, granular in shape and have no preferential orientation (Fig.…”
Section: Macroscopic and Microscopic Aspect Of The Coral Samplesmentioning
confidence: 99%
See 1 more Smart Citation